Fault diagnosis technology overview for lithium‐ion battery energy storage station - Bin Li; Peiyu Chen; Guanzheng Li; Chao Li; Kaidi Zeng; Bin Liu; Xuebin Li; Qidi Huo; Kui Jiao; Chengshan Wang (IET Energy Systems Integration)
Abstract With an increasing number of lithium‐ion battery (LIB) energy storage station being built globally, safety accidents occur frequently. Diagnosing faults accurately and quickly can effectively avoid safe accidents. However, few studies have provided a detailed summary of lithium‐ion battery energy storage station fault diagnosis methods. In this paper, an overview of topologies, protection equipment, data acquisition and data transmission systems is firstly presented, which is related to the safety of the LIB energy storage power station. Then, existing fault diagnosis technologies are reviewed in detail. Finally, the future developing trends of fault diagnosis technology are discussed.